Volatile organic compound emissions from almond shoots during spring—dissociation between reproductive and vegetative organs - Leconte, Anjélica; Barthes, Nicolas; Buatois, Bruno; Coutagne, Eugénie; Duval, Henri; Lucas, Philippe; Staudt, Michael (Comptes Rendus. Chimie)
Prunus dulcis, a fruit tree of global economic and nutritional importance, is infested by Eurytoma amygdali, the almond wasp, due to the lack of biocontrol measures. This study characterizes the volatile organic compounds (VOCs) emitted by almond trees. We identified and quantified by GC-MS 44 VOCs emitted during spring. VOCs emitted during flowering were benzaldehyde and 1,4-dimethoxybenzene, while VOCs emitted during fruit and leaf growth were mainly sesquiterpenes. Emissions increased with temperature but light did not affect short-term emissions. VOCs identified in this study could be used to develop a biocontrol method to prevent infestation.